Improving the Condition of European Hare Through Nutrition - Ernst Martin; Maděra Petr; Frantík Tomáš; Novák Jan; Vencl Štěpán (Journal of Landscape Ecology, 2021)
The objective of the article is to evaluate the effects of a newly designed granulated mixture enriched with Bohemian knotweed (Reynoutria x bohemica) on European hare (Lepus europaeus) kept at closed farms. The positive influence of knotweed on the microbiome in the digestive system and better usage of the fodder were proven based on biochemical and haematological analysis of blood. Lower manifestation of pathogenic organisms is also expected. Finally, the positive influence on higher weight gains in baby hares was proven, which improves their condition. The results can be used in practice at closed farms breeding European hare focused on releasing bred young hares into open hunting grounds where it is possible to obtain a monetary contribution for the releasing of hares from a grant of the Ministry of Agriculture of the Czech Republic in the field of hunting. Furthermore, the results can be used for feeding hares in open hunting grounds.